MicroRNA-130b is involved in bovine granulosa and cumulus cells function, oocyte maturation and blastocyst formation - Sinha, Pritam Bala (J Ovarian Res, 2017)
BACKGROUND: Oocyte maturation and preimplantation embryo development are controlled by array of genes that are post-transcriptionally regulated by microRNAs. With respect to this, previously, we identified altered expression of microRNA-130b (miR-130b) during oocyte maturation. Here, we aimed to investigate the role of miR-130b in bovine granulosa and cumulus cell function, oocyte maturation and preimplantation embryo development using gain- and loss-of- function approach. METHODS: For this study, the granulosa cells, cumulus cells and the oocytes were collected from ovaries obtained from slaughterhouse. The genes targeted by miR-130b were identified using dual-luciferase reporter assay. The role of miR-130b in granulosa and cumulus cell function was investigated by increasing and inhibiting its expression in in vitro cultured cells using miR-130b precursor and inhibitor, respectively while the role of miR-130b on oocyte development, immature oocytes were microinjected with miR-130b precursor and inhibitor and the polar body extrusion, the proportion of oocytes reaching to metaphase II stage and the mitochondrial were determined in each oocyte group 22 h after microinjection. Moreover, to investigate the role of miR-130b during preimplantation embryo development, zygote stage embryos were microinjected with miR-130b precursor or inhibitor and the cleavage rate, morula and blastocyst formation was analyzed in embryos derived from each zygote group after in vitro culture. RESULTS: The luciferase assay showed that SMAD5 and MSK1 genes were identified as the direct targets of miR-130b. Overexpression of miR-130b increased the granulosa and cumulus cell proliferation, while inhibition showed the opposite phenotype. Apart from these, modulation of miR-130b altered the lactate production and cholesterol biosynthesis in cumulus cells. Furthermore, inhibition of miR-130b expression during oocyte in vitro maturation reduced the first polar body extrusion, the proportion of oocytes reaching to metaphase II stage and the mitochondrial activity, while inhibition of miR-130b during preimplantation embryo development significantly reduced morula and blastocyst formation. CONCLUSION: This study demonstrated that in vitro functional modulation of miR-130b affected granulosa and cumulus cell proliferation and survival, oocyte maturation, morula and blastocyst formation suggesting that miR-130b is involved in bovine oocyte maturation and preimplantation embryo development. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13048-017-0336-1) contains supplementary material, which is available to authorized users.